Pelatihan Multimedia Pembelajaran al-Islam dan Kemuhammadiyah (AIK) berbasis website pada MGMP ISMUBA SMP/MTs Kabupaten Banyumas - Havidz Cahya Pratama; A. Sulaeman; Irham Muhammad Azama; Riko Adi Viantoro; Fikri Awang Royani (Jurnal Surya Masyarakat, 2022)
Educators always strive to present learning materials optimally and are supported by adequate learning resources so students can master them completely. This is intended to equip partners by a) instilling awareness in training participants about the importance of developing learning multimedia; b) providing an understanding and insight into the multimedia concept of AIK learning for educators as a special feature of Muhammadiyah schools; 3) providing capabilities and skills in developing web-based learning multimedia to improve the quality of learning and teaching. Partners involved in this training activity are Ismuba teachers of SMP/MTs Muhammadiyah Kab. Banyumas with representatives of each school as many as 20 people. Implementation method with lecture, practice, and assignment methods. The steps of this training activity are divided into two theoretical, drill and demontration sessions, namely: the first theory, the urgency of PAI learning media (curriculum analysis). The second is the concept of AIK learning multimedia. And practice sessions, making website-based AIK learning multimedia using the Canva for Education platform. The results of the service, a) understanding of the learning media showed the pretest value of 88.9% increased to 94.4% for the post-test value. The training instills a common awareness that teachers' enthusiasm to find creative ideas about media designs or plans regarding the material needs to be trained on an ongoing basis. b) Mastering participants' abilities in website-based learning media using the Canva for Education platform has a tendency to increase activity and seriousness, making 22.2% more frequent in use. Supported by the success of the multimedia training, it is also proven by the increase in knowledge and skills by as much as 94.4%.